Ports of Roman Africa : structures and representations - (:unkn) unknown (My University, 2023)
Our survey lists the Roman ports that were built in all the African provinces, from the Atlantic coasts (Mauretania Tingitana) to the « Altars of the Philenes » in the Gulf of Syrtes (Tripolitania) and this, from the fall of Carthage in 146 B.C., with the catch of this one by the Vandals in 439 A.D. It is based on an important corpus of sources, which brings together literary and geographical texts, archaeological, iconographic and epigraphic data. The fertility of the territory of Roman Africa, already known in the Archaic period, contributed to the development of Mediterranean maritime trade, especially that which was bound for Rome. Also, the question of the development of the African coast in Roman times arises, both from a structural and functional point of view, as does that of the Phoenician-Punic maritime heritage. Our work seeks to define the Roman port by a study of ancient and modern terminology, while taking into account its natural environment, its maritime space and its trade network. African ports have completely original port infrastructures. The specificity of Roman port architecture, in its technical aspects or in the design of its facilities, is evident, as shown by the typology of maritime infrastructures (piers, quays, harbor basins, slipways) and that of land infrastructures (lighthouses, storage buildings, buildings related to the stewardship of the voyage), which complete the port capacity. This first synthesis on the Roman ports of Africa proposes a spatio-temporal distribution of the sites and their activities, as well as a better knowledge of their actors. It strives to put Roman Africa and its port networks back at the heart of the Mediterranean maritime world.
Keywords: African Research